Analisis Swot Umkm Azkia Collection Di Cikarang Selatan - Azhar, Alfiyyah; Daspar Daspar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Azkia Collection is one of the Micro, Small, and Medium Enterprise (MSME) that focuses on the Muslim fashion sector. This MSME has an important role in supporting the economic growth of the community and meeting the market's need for fashionable and affordable Muslim clothing. The purpose of this study is to analyze the Azkia Collection business development strategy through the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach. This research applies a qualitative descriptive approach with data obtained through observation, interviews, and documentation study. Based on the research result, it can be seen that Azkia Collection excels in active digital promotion, use of endorsement services, and high customer loyalty. However, weaknesses were also found such as limited capital, the absence of an independent production system, and price differences between online and offline stores. From various external aspects, opportunities come from the increasing trend of Muslim fashion and a wide reseller network while threats include price competition and the emergence of new competitors. The strategy that can be applied is a growth-oriented strategy by utilizing internal strengths and market opportunities to develop the business sustainably.